Development, validation and evaluation of the modified basic life support training (mblst) on the knowledge, practice and confidence levels among nurses in Jordanian government hospitals - Wardeh, Yousef Shukry Mohammad Abu- (2024)
Exemplary educators use simulation and modern facilities to enhance the BLS knowledge, practice, and confidence of newly employed nurses. To support this, a study was conducted to develop, validate, and evaluate the modified Basic Life Support Training (MBLST) for newly employed nurses in Jordanian governmental hospitals. The study has two phases. Phase one involved the development and validation of the MBLST module, based on the American Heart Association's 2020 training materials update, a literature review, and the integration of Miller's Pyramid and Kolb's Cycle as theoretical models. Experts at the Jordanian AHA-BLS training center and potential users evaluated the study's content and face validity. Phase two used a randomized control trial (RCT) with two groups: the intervention group (n = 51) and the control group (n = 51). The trainer implemented the MBLST module for the intervention group and used standard brochures for the control group. After the study, the control group was placed on a waiting list for the MBLST module. Repeated assessments included a pre-test, an immediate post-test after the intervention, and a late post-test three months later. One-way repeated measures ANOVA showed that the MBLST module significantly improved BLS knowledge (F (2,182) = 58.514; p < 0.001), practice (F (2,182) = 20.134; p < 0.001), and confidence (F (2,182) = 37.969; p < 0.001) when comparing pre-test and post-test results. Additionally, the researcher found that the MBLST module had a large effect (Cohen’s d >1) when comparing pre test and post-test results between the control and intervention groups. In summary, the MBLST module was an effective method for improving BLS knowledge, practice, and confidence among newly employed nurses. This study is the first in Jordan to assess these variables and serves as an evidence-based tool for future research on simulation in nursing training.